1996
DOI: 10.1007/bf02284826
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural evidence for the lack of co-transport of B-50/GAP-43 and calmodulin in myelinated axons of the regenerating rat sciatic nerve

Abstract: Following peripheral nerve injury, neurons respond with synthesis of proteins required for axonal regeneration. Newly synthesized membrane proteins, like B-50/GAP-43, are transported with the fast component of anterograde axonal transport. Structural proteins and calmodulin are transported by the slow component. Since B-50/GAP-43 can bind calmodulin, it has been hypothesised that B-50/GAP-43 may act as a carrier for fast anterograde transport of calmodulin, so that both proteins are delivered rapidly to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Our data indicate that pGAP-43 colocalizes with synaptic vesicles in uPA-treated neurons and that this is followed by synapsin I phosphorylation at Ser-9 and mobilization of synaptic vesicles to the AZ. These observations agree with reports from other groups indicating that, following its association with synaptic vesicles (59,60), pGAP-43 activates the synaptic vesicle cycle and induces release of neurotransmitters (1). Importantly, our results indicate that these events require entry of calcium through open presynaptic NMDA receptors.…”
Section: Upa Regulates Gap-43supporting
confidence: 93%
“…Our data indicate that pGAP-43 colocalizes with synaptic vesicles in uPA-treated neurons and that this is followed by synapsin I phosphorylation at Ser-9 and mobilization of synaptic vesicles to the AZ. These observations agree with reports from other groups indicating that, following its association with synaptic vesicles (59,60), pGAP-43 activates the synaptic vesicle cycle and induces release of neurotransmitters (1). Importantly, our results indicate that these events require entry of calcium through open presynaptic NMDA receptors.…”
Section: Upa Regulates Gap-43supporting
confidence: 93%
“…Previous electron microscopic studies revealed that the majority of GAP43 is associated with the plasma membrane and that only ∼25% of GAP43 is associated with vesicles (Verkade et al ., 1996b). This poses the question of how GAP43 gets sorted to the distal process under conditions in which only a minority is localized to vesicles at steady state.…”
Section: Discussionmentioning
confidence: 99%
“…About 30% of GAP43 was found to travel at fast axonal transport rate in regenerating sciatic nerves in vivo (Tetzlaff et al ., 1989), whereas GAP43 was found mostly to be localized at the cytosolic face of the plasma membrane in the adult pyramidal tract (Gorgels et al ., 1989). Ultrastructural analysis revealed that a minor portion of GAP43 is also associated with vesicles (Verkade et al ., 1996b), where it colocalizes with the synaptic vesicle marker synaptophysin (Verkade et al ., 1996a). This poses the question how GAP43 gets sorted to the distal process under conditions in which only a minority is localized to vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the keyword circle within each cluster is commensurate with the frequency of its appearance (Additional file 3: Table S2). The main terms comprising cluster 1 are "axon" [52,53], "day" [54,55], "immunoreactivity" [56,57] and "glial cell" [58,59]. Meanwhile, cluster 2 is characterized by the core keywords "vesicle" [60][61][62], "source" [63,64], "miRNAs" [65,66] and "biomarker" [67][68][69].…”
Section: Keyword Analysis Of Global Research Keyword Co-existence Net...mentioning
confidence: 99%